Early detection of ventricular arrhythmias in adults with congenital heart disease using an insertable cardiac monitor (EDVA-CHD study). (15th April 2020) - Sakhi, Rafi; Kauling, Robert M.; Theuns, Dominic A.; Szili-Torok, Tamas; Bhagwandien, Rohit E.; van den Bosch, Annemien E.; Cuypers, Judith A.A.E.; Roos-Hesselink, Jolien W.; Yap, Sing-Chien
Abstract: Background: Sudden cardiac death (SCD) due to ventricular arrhythmias (VA) is an important mode of death in adults with congenital heart disease (CHD). Risk stratification is difficult in this heterogeneous population. Insertable cardiac monitors (ICM) may be useful for risk stratification. The purpose of the present study was to evaluate the use of ICM for the detection of VA in adults with CHD. Methods: In this prospective single-center observational study we included consecutive adults with CHD deemed at risk of VA who received an ICM between March 2013 and February 2019. The decision to implant an ICM was made in a Heart Team consisting of a cardiac electrophysiologist and a cardiologist specialized in CHD. Results: A total of 30 patients (mean age, 38 ± 15 years; 50% male) received an ICM. During a median follow-up of 16 months, 8 patients (27%) had documented nonsustained VA. Of these 8 patients, 3 (10%) received a prophylactic ICD. Furthermore, ICM-detected arrhythmias were present in 22 patients (73%) leading to a change in clinical management in 16 patients (53%). Besides the patients receiving an ICD, 10 patients (33%) had a change in their antiarrhythmic drugs, 6 patients (20%) underwent an electrophysiology study, and 1 patient (3%) received a pacemaker. Conclusions: The detection of VA by the ICM contributed to the clinical decision to implant a prophylactic ICD. Furthermore, ICM-detected arrhythmias led to important changes in the clinical management. Therefore, long-term arrhythmia monitoring by an ICM seems valuable for risk stratification in adults with CHD. Highlights: Adults with congenital heart disease may be at risk of ventricular arrhythmias. Insertable cardiac monitors can be used for risk stratification in this population. Detected arrhythmias had therapeutic consequences in a majority of patients.